Analysis of blood glucose distribution characteristics in a health examination population in Chengdu (2007–2015). Issue 49 (December 2017) - Huang, Wenxia; Xu, Wangdong; Zhu, Ping; Yang, Hanwei; Su, Linchong; Tang, Huairong; Liu, Yi
Abstract : Abstract: With socioeconomic growth and cultural changes in China, the level of blood glucose may have changed in recent years. This study aims to detect the blood glucose distribution characteristics with a large size of health examination population. A total of 641, 311 cases (360, 259 males and 281, 052 females) more than 18 years old during 2007 to 2015 were recruited from the Health Examination Center at West China hospital, Sichuan University. The percentage of cases with abnormal glucose level and the mean level of glucose were significantly increased since 2007 to 2015 overall. The percentage of cases with abnormal glucose level in males was significantly higher than that in females every year, and the percentage of cases with abnormal glucose level in aged population was higher than the young population. In addition, the mean level of glucose was higher in aged population with normal level of glucose than the young population with normal level of glucose, and the mean level of glucose was higher in males with normal level of glucose than the females with normal level of glucose. The population showed an increased level of blood glucose. Some preventive action may be adopted early and more attention can be paid to them.